2015
DOI: 10.1039/c4py01588f
|View full text |Cite
|
Sign up to set email alerts
|

Anion conducting multiblock poly(arylene ether sulfone)s containing hydrophilic segments densely functionalized with quaternary ammonium groups

Abstract: The use of methylhydroquinones enables the preparation of block copolymers having phenylene rings with precisely 2, 3 or 4 quaternary ammonium groups. Membrane properties show the importance of controlling the local ionic distribution to reach high anion conductivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 36 publications
1
44
0
Order By: Relevance
“…Moreover, the limited ion dissociation and possible anhydride formation may bring about decreased connectivity of the water channels, as suggested by the SAXS study. A similar phenomenon was also found for a block AEM system reported by Jannasch and co‐workers . The anionic conductivity decreased on increasing the number of QA groups per benzene ring from 2 to 4 at a given IEC, mostly because of the reduced ion dissociation with the increasing proximity of the QA groups.…”
Section: Nanostructured Polymer Membranessupporting
confidence: 84%
“…Moreover, the limited ion dissociation and possible anhydride formation may bring about decreased connectivity of the water channels, as suggested by the SAXS study. A similar phenomenon was also found for a block AEM system reported by Jannasch and co‐workers . The anionic conductivity decreased on increasing the number of QA groups per benzene ring from 2 to 4 at a given IEC, mostly because of the reduced ion dissociation with the increasing proximity of the QA groups.…”
Section: Nanostructured Polymer Membranessupporting
confidence: 84%
“…By comparing the 1 H NMR spectra before and after the treatment we concluded that virtually all Im groups were lost (see Supporting Information, Figure S3). We recently reported on the loss of ~80% of the QA groups of a PAES AEM under the same testing conditions [32]. As a consequence, we have investigated the water uptake and ion conductivity of the present AEMs in the Br -form rather than in the OH -form.…”
Section: Water Uptake and Ion Conductivitymentioning
confidence: 96%
“…Strategies to obtain AEM with ion channels include locating ion-conducting groups at the ends of polymer side chains, synthesizing polymer main chains using multiblock co-polymers containing regions of ion-conducting groups [86,87], monomers with densely functionalized ion-conducting regions on the main chains [88] or separately attaching the hydrophobic side change and ion-conducting group to the polymer backbone [89]. Work by Pan et al and Weiber et al shows that increasing the number of QA groups in the block copolymer or the hydrophobic side chain length improved the membrane's IEC to a certain point, after which the IEC decreased with additional QA groups or chain length [86,89]. This was likely due to the QA group proximity (limited ion-dissociating ability) and the over-assembly of ion clusters that resulted in separate ion-conducting regions.…”
Section: Advancements In Aem Polymer Structurementioning
confidence: 99%